Analysis of patient access to orphan drugs in Turkey - Kockaya, Guvenc; Atalay, Sibel; Oguzhan, Gulpembe; Kurnaz, Mustafa; Okcun, Selin; Sar Gedik, Cigdem; Saylan, Mete; Sencan, Nazli (BMC, 2021)
Background Rare diseases are life-threatening, serious, and chronic conditions that require complex care and have a low prevalence. An estimated one in 15 people worldwide are affected by rare diseases. This study aims to analyze the accessibility, reimbursement status, licensed status, and Anatomical Therapeutic Chemical (ATC) codes of drugs that the European Medicines Agency (EMA) in Turkey considers to be ``orphan{''} pharmaceuticals. Methods The drugs included in this analysis were obtained from the list of orphan drugs published by the EMA. Orphan drugs' accessibility and licensing status in Turkey were obtained from the Health Implementation Communique published by the Social Security Institution (SGK) and the List of Abroad Active Substance and List of Licensed Products published by the Turkey Pharmaceuticals and Medical Devices Agency (TITCK). Descriptive analysis was applied to determine the accessibility status of orphan drugs identified by the EMA in Turkey. Results Based on the EMA, 105 pharmaceuticals were approved with ``orphan drug{''} status except for drugs that have lost orphan drug status, decommissioned in the European Union and withdrawn from the European Community Register by January 2020. Of the 105 rare drugs on the EMA list, 34 were inaccessible in Turkey. Of the 71 available drugs, 23 (32\%) were licensed and 48 (68\%) were unlicensed in Turkey. 17 (74\%) of licensed products and 17 (35\%) of unlicensed products were covered by reimbursement. When orphan drugs' ATC codes were examined, the most common ATC group was found to be ``L-Antineoplastic and Immunomodulatory{''} agents. Conclusion An orphan drug incentive policy is very important to ensure early access to the drugs used to treat rare diseases. Considering the capacity and prices for orphan drugs in Turkey, it can be said that many patients with rare diseases have difficulty in their treatment. It is obvious that such a policy must prepare for the regulation of orphan drugs in Turkey.
Keywords: Rare disease drug; Orphan drug; Orphan drug market